1997
DOI: 10.1073/pnas.94.7.3262
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free tumor antigen peptide-based cancer vaccines

Abstract: The central role that tumor antigen-derived peptides play in induction of antitumor immunity makes them ideal candidates for peptide-based cancer vaccines. We have demonstrated that ''transloading'' is an efficient strategy for importing short peptide ligands into antigen-presenting cells in vitro. Postulating that the transloading procedure might effect peptide uptake by antigen-presenting cells in vivo as well, we tested this approach for the generation of peptidebased cancer vaccines. In the P815 mastocytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 51 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Even if applied in an optimized formulation, a combination of immunodominant melanoma Ag was less potent in inducing systemic antitumor immunity than cellular vaccines consisting of irradiated IL-2-or GM-CSF-secreting tumor variants. 32 The efficiency of peptide vaccines may be improved as soon as more immunodominant peptides have been identified and their introduction in the host Ag-presenting system is optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Even if applied in an optimized formulation, a combination of immunodominant melanoma Ag was less potent in inducing systemic antitumor immunity than cellular vaccines consisting of irradiated IL-2-or GM-CSF-secreting tumor variants. 32 The efficiency of peptide vaccines may be improved as soon as more immunodominant peptides have been identified and their introduction in the host Ag-presenting system is optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Local administration of Imiquimod induces a Th1-conducive cytokine storm that includes IFN-␣, TNF-␣, IL-1␣, IL-6, and IL-8 (28 -30), and causes the emigration of resident Langerhans cells from the treated site (31). Poly-arg was shown to enhance the immunogenicity and anticancer activities of peptide Ags (32,33). Fig.…”
Section: Immature DC Injected Into Adjuvant-treated Skin Acquire Migrmentioning
confidence: 99%
“…It has been shown that a complex mixture of tumor peptides conjugated to beads can prime a CTL response in healthy individuals (3), and lipid compounds have been reported to have adjuvant qualities (4). Yet, the most common adjuvant of T cell responses used to date is IFA.…”
mentioning
confidence: 99%